The effect of ethnicity on in-hospital mortality following emergency abdominal surgery: a national cohort study using Hospital Episode Statistics. Issue 11 (November 2015) - Vohra, R.S.; Evison, F.; Bejaj, I.; Ray, D.; Patel, P.; Pinkney, T.D.
Abstract: Objectives: Ethnicity has complex effects on health and the delivery of health care in part related to language and cultural barriers. This may be important in patients requiring emergency abdominal surgery where delays have profound impact on outcomes. The aim here was to test if variations in outcomes (e.g. in-hospital mortality) exist by ethnic group following emergency abdominal surgery. Study design: Retrospective cohort study using population-level routinely collected administrative data from England (Hospital Episode Statistics). Methods: Adult patients undergoing emergency abdominal operations between April 2008 and March 2012 were identified. Operations were divided into: 'major', 'hepatobiliary' or 'appendectomy/minor'. The primary outcome was all cause in-hospital mortality. Univariable and multivariable analysis odds ratios (OR with 95% confidence intervals, CI) adjusting for selected factors were performed. Results: 359, 917 patients were identified and 80.7% of patients were White British, 4.7% White (Other), 2.4% Afro-Caribbean, 1.6% Indian, 2.6% Chinese, 3.1% Asian (Other) and 4.9% not known, with crude in-hospital mortality rates of 4.4%, 3.1%, 2.0%, 2.6%, 1.6%, 1.7% and 5.17%, respectively. The majority of patients underwent appendectomy/minor (61.9%) compared to major (20.9%) or hepatobiliary (17.2%) operations ( P  < 0.001) with an in-hospital mortality of 1.7%, 11.5% and 3.9% respectively. Adjusted mortality was largely similar across ethnic groups except where ethnicity was not recorded (compared to White British patients following major surgery OR 2.05, 95% 1.82–2.31, P  < 0.01, hepatobiliary surgery OR 2.78, 95% CI 2.31–3.36, P  = 0.01 and appendectomy/minor surgery OR 1.78, 95% 1.52–2.08, P  < 0.01). Conclusions: Ethnicity is not associated with poorer outcomes following emergency abdominal surgery. However, ethnicity is not recorded in 5% of this cohort and this represents an important, yet un-definable, group with significantly poorer outcomes. Highlights: Ethnicity has complex effects on delivery of health care in part related to language barriers. Important in emergency abdominal surgery where delays impact on outcomes (e.g. mortality). Population data suggest ethnicity is not linked with poorer outcomes in this cohort. Ethnicity is not recorded in 5% of this cohort. This represents an important, un-definable group with poorer outcomes.